Pemanfaatan Membran Selulosa Bakteri dari Limbah Kulit Pisang sebagai Matriks Masker Antioksidan - Wibowo, Claudia Shinta Octa; Hidayat, Muslikhin; Sulistyo, Hary (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Banana skins have several potential applications in the health and beauty industries. Through a fermentation process with the help of Acetobacter xylinum, it produces banana skin bacterial cellulose. It is possible to further process this cellulose into a face mask matrix. Bacterial cellulose has biodegradable properties, a low toxicity value, and a good absorption ability to be applied as a face mask matrix. The addition of serum to the mask matrix aims to focus on the function of the formulated matrix. Methods: filtering the sample; making nata de banana skin with different fermentation times; making a matrix mask; matrix mask characterization; and data analysis. The results of the study showed that the variation of different fermentation times can affect the resulting cellulose products. The optimal fermentation time for producing nata was 10 days, resulting in a thickness of 0.92 cm. Then, the evaluation tensile strength test on the mask matrix revealed the highest value was also a 10-day fermentation variation, 3.000–10.000 kg/cm2. And last, the best test of the release of vitamin C is the 10-day fermentation variation.